ARTISTIC AND HISTORICAL VALUE OF THE NOVEL BY JUMANIYAZ SHARIPOV «KHOREZM» (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
This article examines the creative and scientific work of the famous Uzbek scholar, literary scholar, poet, writer and translator Jumaniyaz Sharipov. It analyzes his novel "Khorezm", created on a documentary basis and being a kind of chronicle of the life of the Khorezmians in the pre-revolutionary and first revolutionary years.